2017
DOI: 10.3390/ijms18112410
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of STAT3 in Subcutaneous Adipose Tissue Associates with Cardiovascular Risk in Women with Rheumatoid Arthritis

Abstract: Despite the predominance of female patients and uncommon obesity, rheumatoid arthritis (RA) is tightly connected to increased cardiovascular morbidity. The aim of this study was to investigate transcriptional activity in the subcutaneous white adipose tissue (WAT) with respect to this disproportionate cardiovascular risk (CVR) in RA. CVR was estimated in 182 female patients, using the modified Systematic Coronary Risk Evaluation scale, and identified 93 patients with increased CVR. The overall transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Interestingly, the upregulation of STATs caused by pro‐inflammatory cytokines or growth factors is conductive to the pathogenesis of RA 42 . Besides, multiple lines of evidences have revealed that high expression of STAT3 contributes to the development of RA 43‐45 . More importantly, previously conducted study has suggested lncRNA XIST upregulates STAT3 to facilitate the development of retinoblastoma through binding with miR‐124 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the upregulation of STATs caused by pro‐inflammatory cytokines or growth factors is conductive to the pathogenesis of RA 42 . Besides, multiple lines of evidences have revealed that high expression of STAT3 contributes to the development of RA 43‐45 . More importantly, previously conducted study has suggested lncRNA XIST upregulates STAT3 to facilitate the development of retinoblastoma through binding with miR‐124 46 .…”
Section: Discussionmentioning
confidence: 99%
“…42 Besides, multiple lines of evidences have revealed that high expression of STAT3 contributes to the development of RA. [43][44][45] More importantly, previously conducted study has suggested lncRNA XIST upregulates STAT3 to facilitate the development of retinoblastoma through binding with miR-124. 46 All these findings provided strong support for our results that lncRNA XIST bound to let-7c-5p to upregulate STAT3 expression in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary DNA was synthesized using High Capacity cDNA Reverse Transcription kit (Applied Biosystems, Foster City, CA). Amplification of the gene product was attained on a ViiA™7 Real-Time PCR (Applied Biosystems) using SYBR Green qPCR Mastermix (SA Biosciences, Qiagen) and primer pairs as reported [33, 40]. Gene expression levels were calculated by the ddCt method and presented as relative quantity to the average expression in the IGF1 hi group.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of adipokines and cytokines were determined using specific sandwich ELISA kits according to the instructions from the manufacturers (R&D Systems, Minneapolis, MN, USA) as previously described ( 28 ). The inflammatory parameters, blood lipids and RF/ACPA antibodies were measured at the accredited Laboratory of Clinical Chemistry at the Sahlgrenska University Hospital according to clinical routines.…”
Section: Methodsmentioning
confidence: 99%